3D Hybrid Plasmonic Photonic Crystals by Colloidal‐Crystal Templating and Hydrogel‐Assisted Conformal Metal Etching. Issue 20 (26th July 2019) - Geng, Chenyan; Sun, Haiyan; Ma, Lihui; Ling, Cheng; Fu, Ming; He, Dawei; Wang, Yongsheng
Abstract: The development of efficient colloidal templating methods for nanophotonic structures, leading to 3D synergy of photonic crystal behavior with uniform plasmonic resonances is significant, yet challenging. In this work, uniform Ag or Ni octahedral particles with 3D periodicity derived from dissociation of metallic inverse opals are dispersed in hydrogel by conformal etching. The hydrogel can maintain the position of the dissociated metal particles and does not hinder ion transport during the two‐step cyclic electrochemical process. Bragg peaks from the 3D behavior of the colloidal photonic crystals appear due to the reduced filling fraction of metals and are affected by the existence of localized plasmonic resonance (LSPR). LSPR is supported at frequencies ranging from near‐infrared to near‐ultraviolet due to the geometry of the dissociated metal particles. Dissociation of inverse opals during etching is monitored by examining their morphologies, cycle‐related variations in the electrochemical current density, cycle‐related increases of transmission intensities, and redshifts of the Bragg peak wavelengths due to an increased lattice constant in high pH solutions. Ag plasmonic photonic crystals filled with functional polymethacrylic acid and polyacrylamidophenylboronic acid hydrogels function as pH and glucose sensors. The sensitivity increases when plasmonic resonances affect the Bragg peaks. Abstract : Hybrid photonic crystals with uniform 3D plasmonic resonance are fabricated using colloidal‐crystal templating and hydrogel‐assisted conformal metal etching. Localized plasmonic resonance (LSPR) is supported at frequencies ranging from near‐infrared to near‐ultraviolet, and the LSPR interacts with the photonic bandgap in the 3D periodic structures. The sensitivity increases when plasmonic resonances affect the Bragg peaks.